2017
DOI: 10.1016/j.cognition.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of semantic neighborhood density in abstract and concrete words

Abstract: Concrete and abstract words are thought to differ along several psycholinguistic variables, such as frequency and emotional content. Here, we consider another variable, semantic neighborhood density, which has received much less attention, likely because semantic neighborhoods of abstract words are difficult to measure. Using a corpus-based method that creates representations of words that emphasize featural information, the current investigation explores the relationship between neighborhood density and concr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
(54 reference statements)
0
25
0
1
Order By: Relevance
“…Emotional arousal and valence are often cited as playing a critical role in the difference between abstract semantics and concrete semantics [7,81,82]. Abstract words, in general, tend to be more emotionally valenced than concrete words [83] and, within the domain of abstract words, highly arousing words elicit different behaviours from emotionally neutral words; the distribution of lexical decision reaction times is narrower and earlier for emotional words [84].…”
Section: Emotion Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…Emotional arousal and valence are often cited as playing a critical role in the difference between abstract semantics and concrete semantics [7,81,82]. Abstract words, in general, tend to be more emotionally valenced than concrete words [83] and, within the domain of abstract words, highly arousing words elicit different behaviours from emotionally neutral words; the distribution of lexical decision reaction times is narrower and earlier for emotional words [84].…”
Section: Emotion Conceptsmentioning
confidence: 99%
“…Semantic richness may be largely a matter of the methods used to measure it, which may be more or less suitable for certain types of concepts. The apparent semantic poverty of abstract concepts may be an artefact of methods suited to evaluating concrete concepts [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Danguecan and Buchanan (2016) found that the SND effect (operationalized using WINDSOR; Macdonald, 2013) were consistent for abstract words in comparison to inconsistent SND effect for concrete words across different processing tasks (lexical decision, sentence relatedness, and progressive demasking). As such, the findings of Mirman and Magnuson are only limited to concrete words that have been shown to have inconsistent (or lack of) SND effect compared to abstract words (see Reilly & Desai, 2017).…”
Section: Empirical Studies On the Effects Of Sndmentioning
confidence: 99%
“…Word selection and production can be influenced by several psycholinguistics factors such as word frequency or age of acquisition (e.g. Alario et al, 2004;Newman & German, 2005;Barry et al, 2006;Perret & Bonin, 2018;Rabovsky et al, 2016), or by factors related to the semantic network (Meyer & Schvaneveldt 1971;Ferrand & New, 2003;McRae et al, 2012;Reilly & Desai, 2017;Tree & Hirsh, 2003;Gordon & Cheimariou, 2013). Word production also undergoes changes during lifespan and therefore varies according to the age of the speaker (Kavé et al, 2010;Laganaro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%